دور الإتصال الرقمي في حوكمة أنشطة الجمعيات دراسة ميدانية على جمعيات المجتمع المدني بولاية سوق اهراس - شابي سميحة; ضرباني نادية (My University, 2022)
Abstract: This study aimed at identifying the role of digital communication in the governance of the activities of associations in Algeria, through an attempt to understand, extrapolate and interpret its exploratory and explanatory descriptive aspects, starting from conducting a comprehensive survey on Algerian national associations active in Souk Ahras, represented in 12 respondents of its leaders (heads of associations) and a comprehensive survey of the contents of its Facebook pages, using a veriety of data collection tools: qualitative (participatory observation, exploratory interviews, qualitative level in content analysis) as well as quantitative (quantitative level in content analysis), within the framework of the mixed methodological approach in order to achieve the objectives of the study in all its stages, using the appropriate social survey method for this type of descriptive studies. Accordingly, this study is based in its approach to reality on the communicative approaches of two main theoretical approaches (management by objectives, and situational perspectives) which employs them together to approach the subject of the study. ------------------------------------- Abstract: This study aimed at identifying the role of digital communication in the governance of the activities of associations in Algeria, through an attempt to understand, extrapolate and interpret its exploratory and explanatory descriptive aspects, starting from conducting a comprehensive survey on Algerian national associations active in Souk Ahras, represented in 12 respondents of its leaders (heads of associations) and a comprehensive survey of the contents of its Facebook pages, using a veriety of data collection tools: qualitative (participatory observation, exploratory interviews, qualitative level in content analysis) as well as quantitative (quantitative level in content analysis), within the framework of the mixed methodological approach in order to achieve the objectives of the study in all its stages, using the appropriate social survey method for this type of descriptive studies. Accordingly, this study is based in its approach to reality on the communicative approaches of two main theoretical approaches (management by objectives, and situational perspectives) which employs them together to approach the subject of the study. ----------------------------------------- ملخص: هدفت هذه الدراسة إلى تحديد دور الاتصال الرقمي في حوكمة أنشطة الجمعيات في الجزائر، من خلال محاولة فهمه واستقراءه وتفسير جوانبه الوصفية الاستكشافية والتفسيرية، انطلاقًا من إجراء مسح شامل للجمعيات الوطنية الجزائرية الناشطة في ولاية سوق أهراس، ممثلةً في 12 مستجيبًا من قياداتها (رؤساء الجمعيات)، ومسح شامل لمحتويات صفحاتها على فيسبوك، باستخدام أدوات جمع بيانات متنوعة: نوعية (الملاحظة التشاركية، المقابلات الاستكشافية، المستوى النوعي في تحليل المحتوى)، وكمية (المستوى الكمي في تحليل المحتوى)، في إطار المنهج المختلط، وذلك لتحقيق أهداف الدراسة في جميع مراحلها، باستخدام منهج المسح الاجتماعي المناسب لهذا النوع من الدراسات الوصفية. وعليه، تعتمد هذه الدراسة في مقاربتها للواقع على المقاربات التواصلية لمنهجين نظريين رئيسيين (الإدارة بالأهداف، والمنظورات الظرفية)، موظّفةً إياهما معًا في مقاربة موضوع الدراسة. ------------------------------------------- Résumé : Cette étude visait à identifier le rôle de la communication numérique dans la gouvernance des activités associatives en Algérie. Elle visait à comprendre, extrapoler et interpréter ses aspects descriptifs exploratoires et explicatifs. Elle s’appuyait sur une enquête exhaustive auprès des associations nationales algériennes actives à Souk Ahras, représentées par 12 répondants parmi leurs dirigeants, et sur une étude exhaustive du contenu de leurs pages Facebook. Elle utilisait divers outils de collecte de données : qualitatives (observation participative, entretiens exploratoires, analyse de contenu qualitative) et quantitatives (analyse de contenu quantitative), dans le cadre d’une approche méthodologique mixte. L’objectif était d’atteindre les objectifs de l’étude à toutes les étapes, en utilisant la méthode d’enquête sociale appropriée à ce type d’études descriptives. Ainsi, cette étude s’appuie, dans son approche de la réalité, sur les approches communicationnelles de deux principales approches théoriques (gestion par objectifs et perspectives situationnelles) qu’elle exploite conjointement pour aborder le sujet de l’étude.
Keywords: دور الإتصال الرقمي، حوكمة أنشطة الجمعيات